Variables Affecting Thigh Girth Measurement and Observer Reliability in Dogs - McCarthy, Daniel A.; Millis, Darryl L.; Levine, David; Weigel, Joseph P. (Frontiers in Veterinary Science, 2018)
Objective- The purpose of the study was to describe variables affecting thigh girth measurements preoperatively and two weeks after surgical stabilization of the stifle and to examine inter- and intra-observer reliability. Animals- Ten hound-type dogs with expiermental unilateral, cranial cruciate ligament transection and surgical stabilization. Procedures- Dogs were placed in lateral recumbency for measurements of thigh circumference after stifle placement in flexed (F), estimated standing (S), and extended (E) positions. Measurements were made at 50 and 70% of thigh length (TL), with hair unclipped and clipped pre-surgery, before and 2 weeks after cruciate ligament transection and stifle stabilization, and with and without sedation. All measurements were made by two blinded individuals in triplicate, data were recorded for each set of measurements and the mean of the three measurements for each condition was used for analysis. Results- Thigh girth was significantly greater at the more proximal site of 50% TL (36.7 +/- 2.6 cm) when compared to the 70% TL (31.7 +/-2.7 cm) (P=0.001). Sedation did not significantly affect thigh girth at the 70% and 50% TL. Although there were no differences in thigh circumference between the flexion and standing positions at 50% TL (F 38.2 +/- 2.8 cm, S 38.1 +/- 2.9 cm) and 70% TL (F 33.6 +/- 1.6 cm; S 33.6 +/- 1.8 cm), full extension of the stifle resulted in significantly less thigh girth (50% TL 36.6 cm +/-2.6 cm, P=0.006 ; 70% TL 31.7 +/-2.6 cm, P=0.006). Significant decreases in thigh girth were seen after surgery in all limb positions at both measurement sites. The highest correlations between Observer 1 (OB1) and Observer 2 (OB2) with least differences in measurements were with the stifle in the extended position. Agreement between two observers using standard measuring technique was significant at both the 50% (OB1: 34.10±2.93 cm, OB2: 34.08±2.65 cm, P=0.004, ICC=0.984) and 70% (OB1: 29.89±2.43 cm, OB2: 30.04±2.30 cm, P=0.007, ICC=0.981) TL. Conc. Thigh girth measurement is a repeatable and reliable possible outcome measure. Thigh girth should be obtained at a distance of 70% thigh length, with the stifle in extension, and the patient relatively calm.